USE OF NON-TRADITIONAL METHODS IN THE MENTAL EDUCATION OF PRESCHOOL CHILDREN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This article discusses the importance of educational games in the mental development of preschool children, the practical aspects of non-traditional methods.